2010
DOI: 10.1016/j.vetmic.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Virological and pathological findings in Bluetongue virus serotype 8 infected sheep

Abstract: Twenty-seven sheep of the four most common Swiss breeds and the English breed Poll Dorset were experimentally infected with a northern European field strain of bluetongue virus serotype 8 (BTV-8). Animals of all breeds eveloped clinical signs, viremia and pathological lesions, demonstrating that BTV-8 is fully capable of replicating and inducing bluetongue disease (BT) in the investigated sheep. Necropsy performed between 10 and 16 days post-infectionem (d.p.i.) revealed BT-typical hemorrhages, effusions, edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
2
32
1
3
Order By: Relevance
“…The results showed that oral and intravenous infection of BTV-8 produce the same tissue lesions in IFNAR (2/2) mice (Calvo-Pinilla et al, 2009a), regardless of the mode of infection. In addition, these microscopic lesions are similar to those observed in the natural host (Maclachlan et al, 2009;Worwa et al, 2010). To confirm that BTV-8 replicates in these tissues, immunohistochemistry with a hyperimmune serum from a BTV-8-infected cow was performed as described by Sanchez-Cordon et al (2010).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…The results showed that oral and intravenous infection of BTV-8 produce the same tissue lesions in IFNAR (2/2) mice (Calvo-Pinilla et al, 2009a), regardless of the mode of infection. In addition, these microscopic lesions are similar to those observed in the natural host (Maclachlan et al, 2009;Worwa et al, 2010). To confirm that BTV-8 replicates in these tissues, immunohistochemistry with a hyperimmune serum from a BTV-8-infected cow was performed as described by Sanchez-Cordon et al (2010).…”
mentioning
confidence: 58%
“…No infectious virus was detected in the other tissues analysed. The same viral tropism has been observed in IFNAR (2/2) mice infected intravenously with BTV (Calvo-Pinilla et al, 2009a) and in naturally BTVinfected calves and sheep where high titres of BTV are present in lung, precapsular and mesenteric lymph nodes, thymus and spleen, which are secondary sites of BTV replication (Barratt-Boyes & MacLachlan, 1994, 1995Hemati et al, 2009;MacLachlan et al, 1990;SanchezCordon et al, 2010;Worwa et al, 2010).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Typical post-mortem pathological findings include oedema and haemorrhages in mesenteric lymph nodes, pulmonary oedema, pleural and pericardial effusions. Additionally, multiple spots of haemorrhages in the pulmonary artery, as well as limited necrosis of myocardium are the histopathological findings most frequently seen Worwa et al, 2010;MacLachlan, 2011).…”
Section: General Features Of Bluetongue Virus and The Diseasementioning
confidence: 99%
“…Sentinel animals were seronegative and virus-free at the beginning of the study. Serum and whole blood were collected weekly from each animal to assay for BTV-specific antibodies and viral nucleic acid, using group-reactive competitive enzyme-linked immunosorbent assay (cELISA; VMRD Inc., Pullman, WA) and RT-qPCR, as previously described (Ortega et al, 2010;Mayo et al, 2010;Worwa et al, 2010;Mayo et al, 2011).…”
Section: A Longitudinal Study Of the Epidemiology Of Btv Infection Inmentioning
confidence: 99%